Pendampingan Pengenalan Surat Surat Pendek Di Pengajian Bu Oyok RT 07 RW 02 Desa Wanawali - Fani Nur Anggraeni; Yuwan Fijar Anugrah; Irma Megawati (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
Mentoring is teaching and coaching. , in Bu Oyok's recitation related to memorizing short letters. The meaning of the letter and the number of verses in the letter are not fully known. Therefore, the aim of this research is to provide assistance in the introduction of short letters using the PAR method. The PAR method involves carrying out research to define a problem and applying information into action as a solution to a defined problem. This activity takes place at Bu Oyok's recitation